Endothelial Progenitor Cells as Prognostic Markers of Preterm Birth‐Associated Complications. (27th July 2016) - Bertagnolli, Mariane; Nuyt, Anne Monique; Thébaud, Bernard; Luu, Thuy Mai
Abstract: Preterm birth is associated with alteration of the vascular tree that can result in disease states such as bronchopulmonary dysplasia and retinopathy of prematurity during the neonatal period and emphysema and hypertension in adulthood. Studies have suggested a potential role for endothelial progenitor cells in the pathophysiology of prematurity‐related complications involving blood vessels; however, this knowledge has never been synthesized. We conducted a systematic review of the published data to examine the characteristics of endothelial progenitor cells in relation to preterm birth in humans. Preterm infants compared with term controls displayed similar or increased circulating/cord blood endothelial progenitor cell counts. However, the preterm endothelial progenitor cells were more vulnerable to exogenous factors such as oxidative stress. A reduced number, in particular of endothelial colony‐forming cells, was associated with bronchopulmonary dysplasia. No studies have examined endothelial progenitor cells beyond the neonatal period. These findings could prove useful in the identification of biomarkers for prognostication or therapeutic strategies for vascular‐related diseases in preterm‐born individuals. Stem Cells Translational Medicine 2017;6:7–13